2016
DOI: 10.1158/1535-7163.mct-16-0176
|View full text |Cite
|
Sign up to set email alerts
|

Targeting Homologous Recombination by Pharmacological Inhibitors Enhances the Killing Response of Glioblastoma Cells Treated with Alkylating Drugs

Abstract: Malignant gliomas exhibit a high level of intrinsic and acquired drug resistance and have a dismal prognosis. First- and second-line therapeutics for glioblastomas are alkylating agents, including the chloroethylating nitrosoureas (CNU) lomustine, nimustine, fotemustine, and carmustine. These agents target the tumor DNA, forming O-chloroethylguanine adducts and secondary DNA interstrand cross-links (ICL). These cross-links are supposed to be converted into DNA double-strand breaks, which trigger cell death pat… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
29
0
1

Year Published

2016
2016
2021
2021

Publication Types

Select...
8
1

Relationship

2
7

Authors

Journals

citations
Cited by 43 publications
(31 citation statements)
references
References 59 publications
1
29
0
1
Order By: Relevance
“…Moreover, the pharmacological inhibition or knockdown of downstream proteins in the HR pathway, such as BRCA2, RAD51, and CHK2, also increased sensitivity to treatment (Quiros et al, 2011;Eich et al, 2013). Furthermore, GBM cells treated with other alkylating agents were more sensitive after inhibition of MRE11, a component of MRN complex that recognizes DNA lesions and recruits ATM kinase (Berte et al, 2016). In contrast, some reports suggest that ATM/ATR activation is required to induce cell death after the MMR futile cycle is established (Caporali et al, 2004) and that MRE11 knockdown decreases sensitivity to TMZ (Mirzoeva et al, 2006).…”
Section: Dna Repair and Gbm Resistance To Treatmentmentioning
confidence: 99%
“…Moreover, the pharmacological inhibition or knockdown of downstream proteins in the HR pathway, such as BRCA2, RAD51, and CHK2, also increased sensitivity to treatment (Quiros et al, 2011;Eich et al, 2013). Furthermore, GBM cells treated with other alkylating agents were more sensitive after inhibition of MRE11, a component of MRN complex that recognizes DNA lesions and recruits ATM kinase (Berte et al, 2016). In contrast, some reports suggest that ATM/ATR activation is required to induce cell death after the MMR futile cycle is established (Caporali et al, 2004) and that MRE11 knockdown decreases sensitivity to TMZ (Mirzoeva et al, 2006).…”
Section: Dna Repair and Gbm Resistance To Treatmentmentioning
confidence: 99%
“…There are very few specific HR inhibitors in pre-clinical development at this time, and most of them appear to inhibit Rad51 (24). Recent studies have suggested that these molecules may be sensitize the effects of alkylators (25) and radiotherapy (26) specifically in glioma. Small molecule inhibitors of canonical NHEJ proteins, such as DNA-PK, have been developed and are now being tested as radiosensitizers in clinical trials, although currently there are no studies specifically in GBM (27).…”
Section: Targeting Nhej and Hr Repairmentioning
confidence: 99%
“…However, DNA repair systems in most HCC cells are abnormally active due to the accumulation of mutations, resulting in elevated DNA repair capacity and poor chemotherapy outcomes. Recent studies have demonstrated that the effects of chemotherapy and radiotherapy can be significantly enhanced when the DNA repair pathway in cancer cells is blocked, and accordingly, DNA repair blockers, such as trans-resveratrol, B02, and IBR2, have been widely used for clinical treatment to reduce the dose of chemotherapeutic drugs and improve their therapeutic effects [ 5 , 6 , 7 ].…”
Section: Introductionmentioning
confidence: 99%